Type I interferon regulates the expression of long non-coding RNAs - Carnero, Elena; Barriocanal, Marina; Segura, Victor; Guruceaga, Elizabeth; Prior, Celia; Börner, Kathleen; Grimm, Dirk; Fortes, Puri (Frontiers in immunology, 2014)
Interferons (IFNs) are key players in the antiviral response. IFN sensing by the cell activates transcription of IFN-stimulated genes (ISGs) able to induce an antiviral state by affecting viral replication and release. IFN also induces the expression of ISGs that function as negative regulators to limit the strength and duration of IFN response. The ISGs identified so far belong to coding genes. However, only a small proportion of the transcriptome corresponds to coding transcripts and it has been estimated that there could be as many coding as long noncoding RNAs (lncRNAs). To address whether IFN can also regulate the expression of lncRNAs, we analyzed the transcriptome of HuH7 cells treated or not with IFNα2 by expression arrays.
Gesehen am 14.10.2020